Curriculum materials as a barrier to the use of communicative approach to English language teaching in EFL context: examples from Tanzania - John Misana Biseko; Majuto Manyilizu; Joshua Andilile Mwaipape; Daud Nyinge; Adriano Utenga (English, 2020)
This paper examines how curriculum materials act as a barrier to implementation of communicative Language Teaching (CLT) in English as a Foreign Language (EFL) context. It has been noted that several studies report some challenges of CLT in English language teaching. Consequently, some authors conclude that CLT is useless while others observe that the reported challenges are external weaknesses caused by users of the approach. In light of this debate, this study was conducted. Two questions were the focus of the study: how do curriculum materials respond to CLT? How does the actual use of the developed curriculum materials respond to principles of CLT? Drawing on the data obtained, authors of this study argue that curriculum materials are missing essential tasks which would facilitate a smooth implementation of CLT. Consequently, features of the traditional methods are dominating the practices. Authors advocate that it is unfair to argue that CLT is useless in EFL context but we have failed to design for it. Following the noted weaknesses, researchers recommend the adoption of task-based curriculum material design to ensure rich communicative activities in textbooks and classrooms as well.